Electronic and spatial control over the formation of transient ion pairs during photoinduced electron transfer between proflavine–amine systems in a subpicosecond time regime. Issue 25 (7th March 2017) - Sengupta, Chaitrali; Mitra, Piyali; Koley Seth, Banabithi; Mandal, Debabrata; Basu, Samita
Abstract : Probing photoinduced electron transfer (PET) in solution in terms of rate of reaction and reaction free energy is a great challenge in physical chemistry. Abstract : Probing photoinduced electron transfer (PET) in solution in terms of rate of reaction and reaction free energy is a great challenge in physical chemistry. Several factors such as solvent polarity, viscosity, and electronic coupling between reacting species control the overall rate of the reaction. However, the unambiguous reaction mechanism is still an important area of research. Earlier, our studies on proflavine–DMA and proflavine–TEA electron donor–acceptor systems revealed the dynamics of the diffusion controlled aspect of PET. Herein, we have extended our investigation in a higher time resolution i.e. in the femtosecond–picosecond timescale to decipher the incidents occurring at the time regime associated with PET. Our present contribution sheds light on the controlling factors of polarity, viscosity, and microheterogeneity, leading to the confinement of reactants at the molecular level. We also tried to qualitatively as well as quantitatively probe these factors. Our present investigation reveals that electron transfer in these two systems is dependent on several factors. In the case of alcoholic solvents, the fastest fluorescence decay components are the result of the formation of a contact ion pair (CIP) as well as direct electron transfer and therefore depend on the dielectric of the medium. On the other hand, in a heterogeneous medium, compartmentalization of reactants and interaction between the components with head groups and tail parts of micelles, depending on the overall charge of a particular micelle, are the controlling factors for the reaction dynamics.